Seroprevalence of severe fever with thrombocytopenia syndrome (SFTS) virus antibodies in humans and animals in Ehime prefecture, Japan, an endemic region of SFTS. Issue 10 (October 2018) - Kimura, Toshiya; Fukuma, Aiko; Shimojima, Masayuki; Yamashita, Yasutaka; Mizota, Fumi; Yamashita, Mayumi; Otsuka, Yuka; Kan, Miki; Fukushi, Shuetsu; Tani, Hideki; Taniguchi, Satoshi; Ogata, Momoko; et al.
Abstract: Severe fever with thrombocytopenia syndrome (SFTS) was first identified as an emerging tick-borne infectious disease caused by the SFTS virus (SFTSV) in China and has also been found to be endemic to Japan and South Korea, indicating that SFTS is of great concern in East Asia. The aim of the present study was to determine the seroprevalence of SFTSV antibodies in humans and animals in SFTS-endemic regions of Japan. One of 694 (0.14%) healthy persons over 50 years of age and 20 of 107 (18.7%) wild and domestic animals in Ehime prefecture of western Japan were determined to be seropositive for SFTSV antibodies by virus neutralization test and ELISA, respectively. The seropositive person, a healthy 74-year-old woman, was a resident of the southwest part of Ehime prefecture engaged in citriculture and field work. This woman's sample exhibited neutralizing activity against SFTSV although she had neither a clear experience with tick bites nor SFTS-like clinical illness. These findings indicate that most people living in the endemic regions are not infected with SFTSV and suggest that most of the SFTS patients reported so far do not reflect the tip of an iceberg of people infected with SFTSV, but at the same time, that SFTSV infection does not always induce severe SFTS-associated symptoms. These findings also suggested that SFTSV has been maintained in nature within animal species and ticks.